A Sore Subject? An Examination of National Case-Based Chancroid Surveillance - Ogale, Yasmin P; Ridpath, Alison D; Torrone, Elizabeth; Quilter, Laura A S; Grey, Jeremy A (Sexually transmitted diseases, 2023)
Chancroid has been a nationally notifiable condition in the United States since 1944, with cases reported to Centers Disease Control and Prevention through the National Notifiable Diseases Surveillance System. Although frequently reported during the 1940s, <20 cases have been reported annually since 2011. We assessed the performance and utility of national case-based chancroid surveillance. We reviewed the literature to contextualize chancroid surveillance through National Notifiable Diseases Surveillance System. We then assessed 4 system attributes, including data quality, sensitivity, usefulness, and representativeness: we reviewed chancroid cases reported during 2011-2020, conducted interviews with (a) sexually transmitted disease programs reporting ≥1 case in 2019 or 2020 (n = 9) and (b) Centers Disease Control and Prevention subject matter experts (n = 10), and reviewed published communicable disease reporting laws. Chancroid diagnostic testing is limited, which affects the surveillance case definition. National case-based surveillance has poor data quality; of the 2019 and preliminary 2020 cases (n = 14), only 3 were verified by jurisdictions as chancroid cases. Sexually transmitted disease programs report the system has low sensitivity given limited clinician knowledge and resources; experts report the system is not useful in guiding national control efforts. Review of reporting laws revealed it is not representative, as chancroid is not a reportable condition nationwide. Critical review of system attributes suggest that national case-based chancroid surveillance data have limited ability to help describe and monitor national trends, and chancroid's inclusion on the national notifiable list might need to be reconsidered. Alternative strategies might be needed to monitor national chancroid burden.